2015
DOI: 10.1590/s1516-89132015050485
|View full text |Cite
|
Sign up to set email alerts
|

Control of Acid Phosphatases Expression from Aspergillus niger by Soil Characteristics

Abstract: This work studied the acid phosphatase (APase) activity from culture medium (extracellular, eAPase)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…It is known that acid phosphatases have their optimum activity in low pH environments (4–6), while alkaline have it in high pH media (8–10). Previous studies showed that pH generally affects the enzymatic activity, in coincidence with our findings (Nahas ). It appears that fungal growth in soils could benefit the acid phosphatase activity over alkaline ones, as they lower the pH even in buffered mediums, turning the environmental conditions more favourable for acid phosphatases, but further experiments should be performed to verify this hypothesis.…”
Section: Discussionsupporting
confidence: 93%
“…It is known that acid phosphatases have their optimum activity in low pH environments (4–6), while alkaline have it in high pH media (8–10). Previous studies showed that pH generally affects the enzymatic activity, in coincidence with our findings (Nahas ). It appears that fungal growth in soils could benefit the acid phosphatase activity over alkaline ones, as they lower the pH even in buffered mediums, turning the environmental conditions more favourable for acid phosphatases, but further experiments should be performed to verify this hypothesis.…”
Section: Discussionsupporting
confidence: 93%
“…Niewiadomska [1] observed an analogical effect in the study on alfalfa, where the PRP SOL fertiliser containing phosphorus, potassium, zinc, boron, molybdenum, and other elements decreased the catalytic activity of the enzyme by triggering compounds unavailable to plants. There were similar results in the studies by Nahas [37] and Laishram et al [28]. Lemanowicz and Koper [38] observed greater activity of these enzymes in the experimental variant without phosphorus fertilisation.…”
Section: Biochemical Activity Of Soilsupporting
confidence: 87%
“…niger strains as producing a substantial quantity of acid phosphatase (Nahas, 2015). A. niger PM-4 was found more e cient in producing a higher amount of P as compared to P. aeruginosa CD6C.…”
Section: Nutrients Solubilizationmentioning
confidence: 84%